Preemptive peritonsillar infiltration with bupivacaine in combination with tramadol improves pediatric post-tonsillectomy pain better than using bupivacaine or tramadol alone: A randomized, placebo-controlled, double blind clinical trial - Honarmand, Azim (Adv Biomed Res, 2015)
BACKGROUND: Post-tonsillectomy pain is one of the most common problems after anesthesia, therefore use of a good anesthesia technique with minimum side effect is an important aim. This study was performed to compare the efficacy of peritonsillar infiltration of bupivacaine, tramadol and combination of bupivacaine-tramadol in post-tonsillectomy pain. MATERIALS AND METHODS: In a double blind trial 120 ASA I and II children condidated for tonsillectomy were randomized into four groups: Peritonsillar infiltration with bupivacaine 1 mg/kg in Group B, tramadol 2 mg/kg in Group T, combination of bupivacaine-tramadol in Group BT and saline in Group C was done. RESULTS: Until 60 minutes in the recovery room, control of pain in the first three groups were better than Group C (P < 0.05) and in the third group it was better than others. Four hours after surgery, control of pain was better in the second and third groups in comparison to Groups B and Group C (P <0.05) and was better in the third group in comparison to the second group. Then, 24 hours after that, only in the group III the control of pain was effective (P < 0.05). CONCLUSIONS: In this study we showed that peritonsillar infiltration with combination of bupivacain-tramadol provided less post surgery pain compared with infiltration of bupivacaine and tramadol alone in adenotonsillectomy of children.